DEVELOPMENT POLITICS OF DALIHAN NA TOLU IN THE SOCIAL PERSPECTIVE OF BATAK ANGKOLA PEOPLE - Harahap, Suheri; Alfikri, Muhammad (Universitas Negeri Medan, 2023)
This study aims to describe the development politics of Dalihan Na Tolu in the social perspective of the Angkola Batak indigenous people. Humanist political philosophy in South Tapanuli is very basic to be used as motivation for the younger generation because the beginnings of politics stem from various views on the meaning of power and how life situations are in various countries, as well as the times. This study uses a descriptive qualitative research method. Data collection was carried out by literature study, observation, document analysis, and interviews. The results of the study show that South Tapanulis is an area where the Islamic religion and Angkola culture are very strong with the kinship system